Cocoa processing methods for the production of high quality cocoa in Vietnam : (Agricultural Publishing house, 2008)
This manual is directed at farmers, agricultural extension officers and teaching institution. It is recognised that industry requirements, regarding cocoa attributes, may chang in the future and this manual does serve as a basis for manipulating procedures to suit future needs